A comparative study on whole body vibration (WBV) comfort towards Perodua's compact car model through Monte Carlo simulation - Mohd Zulfadzlie Abdullah (Institute of Engineering Mathematics, Universiti Malaysia Perlis, 2017)
The objectives that are addressed in this study are as follows ; to evaluate the impact of the sources (tire-road interaction and engine transmission) that contributes for vibration that generated in the vehicle cabin ; to measure the level of vibration in the cabin based on experimental analysis through the clustering and classification methods ; to compare the whole body vibration towards Perodua compact car's model for type of road through the data mining approach.